The inclusion of Russian sports paraphernalia in the educational process of the subject "Russian as a foreign language" for students - Lavrushina E.V.; Kharitonova O.V.; Uspenskaya L.I.; Panova L.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study. Thisresearch is aimedatexpanding the use of lexical and grammaticaltoolsrelatedtosportsdiscourseandaffectingstatesymbolsin the process of teachingforeignstudentsinRussianhighereducationalinstitutions. Methods and structure of the study. The study was conductedon the basis of the PlekhanovRussianUniversity of EconomicsinMoscow.Whenanalyzinganddescribingvarioustypes of workwithtextshighlightingexamples of the useornon-use of the flag,coat of arms andanthem by athletesanddelegationsatinternationalsportingevents, general scientificandspecializedmethods were used,includingcomparative,structural,descriptiveandcontextualanalysis. Results and conclusions. The results of the study show that studying the state symbols of the country whose language is being studied, as part of the Russian as a foreign language (RKI) course, helps improve the skills of professional and intercultural communication of foreign students, based on the principles of respect and tolerance for the history and culture of another country. The assimilation of thematic vocabulary and the corresponding grammatical apparatus based on authentic materials enables students to improve their proficiency in the Russian language in line with a communicative and activity-based approach, as well as to form and develop intercultural competence through critical analysis of new regional information.